2015
DOI: 10.1080/19443994.2015.1014856
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization of mesoporous silica MCM-41 with 3-aminopropyltrimethoxysilane for dye removal: kinetic, equilibrium, and thermodynamic studies

Abstract: 2015): Surface functionalization of mesoporous silica MCM-41 with 3-aminopropyltrimethoxysilane for dye removal: kinetic, equilibrium, and thermodynamic studies, Desalination and Water Treatment, A B S T R A C TMesoporous silica MCM-41 was synthesized and functionalized with a silane coupling agent (3-aminopropyltrimethoxysilane, APTMS) for the removal of Acid Blue 25 (AB25, anionic dye) and Methylene Blue (MB, cationic dye) from aqueous solutions as adsorbents. The synthesized (MCM-41) and functionalized (f-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 37 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Figure 3 shows the low angle X-ray diffraction (LXRD) patterns of MCM-41, Sal-MCM-3, Sal-MCM-9, ZnO-MCM-3, and ZnO-MCM-9. Three characteristic peaks are shown in MCM-41, which could be ascribed to the (100), (110), and (200) crystal faces, indicating that the particles had a regular hexagonal pore structure [ 42 ]. The modification of salicylaldimine made the intensity of the low-angle XRD peaks decrease, especially in the (110) and (200) crystal face.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the low angle X-ray diffraction (LXRD) patterns of MCM-41, Sal-MCM-3, Sal-MCM-9, ZnO-MCM-3, and ZnO-MCM-9. Three characteristic peaks are shown in MCM-41, which could be ascribed to the (100), (110), and (200) crystal faces, indicating that the particles had a regular hexagonal pore structure [ 42 ]. The modification of salicylaldimine made the intensity of the low-angle XRD peaks decrease, especially in the (110) and (200) crystal face.…”
Section: Resultsmentioning
confidence: 99%
“…Three characteristic peaks of MCM-41 ascribed to the (100), (110) and (200) crystal face representing the regular hexagonal pore structure [32] still existed in the XRD patterns of PDA–MCM-41, indicating that the regular hexagonal pore structure remained after PDA encapsulation. The strength of the XRD peaks of the (100), (110) and (200) crystal face decreased after encapsulated by PDA, which convinced us that PDA was introduced to the system and decreased its degree of orderliness [33].…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the X-ray diffraction (XRD) patterns of MCM-41, Cu–MCM-41, SA–MCM-41, and CH–Cu–MCM-41. There are three characteristic peaks shown in MCM-41, which could be ascribed to (100), (110), and (200) crystal faces, which indicated that the particles had a regular hexagonal pore structure . As modified by salicylaldehyde, the strength of the XRD peaks decreased, especially in (110) and (200) crystal faces, which proved that APTES was introduced to the system and decreased its degree of orderliness .…”
Section: Resultsmentioning
confidence: 94%